Acute Myocardial Injury Following COVID-19 Vaccination: A Case Report and Review of Current Evidence from Vaccine Adverse Events Reporting System Database. (July 2021) - Deb, Anasua; Abdelmalek, John; Iwuji, Kenneth; Nugent, Kenneth
COVID-19 vaccination related adverse events is an evolving field. Here we present a case of acute myocardial injury that developed as a result of an acute immune response following the second dose of COVID-19 vaccination (Moderna) in a 67-year-old man who presented in acute congestive heart failure. His clinical course improved over 3 days. Review of the Vaccine Adverse Events Reporting System (VAERS) in the Centers for Disease Control and Prevention websites identified 37 vaccine recipients who developed myocarditis as an adverse event following COVID-19 vaccination. With the mass expansion of COVID-19 vaccine administration, physicians need to be vigilant about the possibility of new adverse events.